Acute acalculous cholecystitis due to an incarcerated epigastric hernia. Issue 721 (November 1985) - Goldman, G.; Rafael, A. J.; Hanoch, K.
Abstract : A case of a 96 year old woman with an incarcerated gallbladder in an epigastric hernia causing acute acalculous cholecystitis is described. At operation the gallbladder was replaced in its anatomical site and the hernia was repaired. This unique case of acute acalculous cholecystitis demonstrates cystic duct obstruction and cystic vessel compression as possible aetiologies for this pathology.